Design, Development and Evaluation of Photovoltaic Integrated Solar Greenhouse Dryer for Paddy - Mondru, Madhava; Boreddy, Kavitha (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at College of Agricultural Engineering, Bapatla, Andhra Pradesh, India during the month of January, 2021 to develop photovoltaic power assisted forced circulation solar greenhouse dryer and to evaluate its performance for drying of paddy. A free standing greenhouse structure with arch roof was selected to have high light transmission and low cost of construction. To get adequate and uniform light inside the greenhouse east-west orientation was selected. A frame of solar greenhouse dryer having 4.467 m length, 2.134 m width and 2.591 m height was constructed and was covered with twin wall polycarbonate sheet of 6 mm thickness. Freshly harvested paddy was filled in perforated tray with size 142.5×80×12.5 cm up to 10 cm height the trays were placed in drying chamber consists of three tires and two columns. Forced ventilation was provided with four 40 W DC fans which were powered with two 150 W photovoltaic panels. During drying, the green house and ambient air temperature, relative humidity data was collected at every 1 h interval using data logger, the moisture content of the paddy was determined at every 2 h interval. The paddy was dried till getting 12% (w.b.) final moisture content. The highest greenhouse dryer temperature of 48.1°C was recorded as compared with highest ambient temperature of34.2°C. Moreover, the air flow rate achieved was varied between 75.52‒34.25 m3m-1.In this dryer the paddy was dried from 25.3‒12.0% (w.b.) moisture content in 21 h whereas open sun drying took 28 h of drying time.